2017
DOI: 10.1089/gtmb.2016.0189
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 (IL-6)andIL-10Promoter Region Polymorphisms Are Associated with Risk of Lumbar Disc Herniation in a Northern Chinese Han Population

Abstract: This study demonstrates that genetic variants in the promoter regions of the IL-6 and IL-10 genes are associated with lumbar disc herniation risk in this Northern Chinese Han population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Several studies reported significant associations of SNVs of IL6 , IL10 [32], MMP1 and MMP3 [9] with disc herniation. Some of these variants were intronic variants [32] and some variants were not polymorphic in our population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported significant associations of SNVs of IL6 , IL10 [32], MMP1 and MMP3 [9] with disc herniation. Some of these variants were intronic variants [32] and some variants were not polymorphic in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these variants were intronic variants [32] and some variants were not polymorphic in our population. We have assessed only the exonic variants and the SNVs of the candidate genes of inflammatory, catabolic, anti-catabolic molecules were not associated with the severity of disc herniation (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies demonstrated that IL-10 gene polymorphisms (rs1800871, rs1800896) were associated with LDD susceptibility [13,15]. However, the results were not confirmed by the following studies [14]. Despite extensive research in this field, the results were generally inconsistent and inconclusive.…”
Section: Introductionmentioning
confidence: 86%
“…The result showed that rs13306435 of IL-6 gene was associated with LDD in the Finnish population. Subsequently, other studies contradicted the previous study stating that rs13306435 was not relevant to LDD, but other SNPs (rs1800795, rs1800796, and rs1800797) in the IL-6 gene were relevant to LDD [11,12,14,15]. Moreover, several studies demonstrated that IL-10 gene polymorphisms (rs1800871, rs1800896) were associated with LDD susceptibility [13,15].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation